ORANG TIONGHOA, PERKEBUNAN GAMBIR, LADA DAN KONTESTASI DI TANJUNGPINANG ABAD KE-19 - Saumia, Zulfa, ZS (UI Scholars Hub, 2023)
The Chinese have settled in Bintan Island since Zheng He’s great expeditions in the 15th century. However, large-scale arrivals of the Chinese did not occur until in 1740. They worked as laborers in pepper and gambier plantations that belonged to Buginese nobles. Internal and external changes in the political landscape, as well as land and territorial tenures between the Hokkiens in Tanjungpinang and Teochews in Senggarang, added a new nuance to their roles as middlemen, land owners, and coolies in pepper and gambier plantations. This gave rise to contestation between these two ethnic groups. How did the land tenure process take place? What was the role of the Chinese and the Dutch East Indies government in that contestation? Using the concept of Chinese expansion proposed by Kwee Kui Han, this research found that the Chinese were able to establish very structured and systematic presence in the island, both in its hinterland and coastal areas. This condition made it easier for the Chinese to gain control of the economy. This study used the historical method to reconstruct the Chinese’s roles as intermediary traders and plantation owners, as well as the contestation that occurred in Tanjungpinang in the 19th century. Primary data were obtained from Dutch colonial-era sources and the writings of local and foreign historians in order to generate a more comprehensive picture of the topic.